Effectiveness of matured Morus nigra L. (black mulberry) fruit extract on 2,2-diphenyl-1-picrylhydrazyl (DPPH•) and hydroxyl (OH•) radicals as compared to less matured fruit extract - Aydin, Sevinc; Yilmaz, Okkes; Gokce, Zehra (Academic Journals, 2011)
In this study, we investigated the antioxidant effect of the Morus nigra L. (black mulberry) fruit extracts in 2,2-diphenyl-1-picrylhydrazyl (DPPH center dot) and hydroxyl (OH center dot) radicals environments gathered from the district of Elazig. Fruits were extracted with 80% methanol, and methanolic extract's scavenging effect of DPPH center dot radical was examined depending on the quantity. It was observed that less matured fruit extract's (SMF) radical scavenging activity increased from the 50 to 250 mu L, but decreased after 500 mu L (p<0,001). As for matured fruits (MF), the most scavenging activity were observed in 50 and 100 mu L extracts on DPPH center dot and after 250 mu L, it decreased (p<0,001). Methanol phases of extracts by evaporation were dissolved in dimethyl sulfoxide (DMSO) in the environment in which with Fenton reaction, OH center dot radical is constituted; preventing the formation of lipopolysaccharide (LPO) and protective effect on unsaturated fatty acid were examined. In the Fenton reagent environment, preventing effect on the formation of LPO, it was determined that MF extract was more effectual than SMF extract (p<0,001). Accordingly, it was established that M. nigra fruit extract has protecting effect on unsaturated fatty acids (p<0,001). We considered that fruit extracts having scavenging effects on DPPH center dot radical and diminishing the formation of LPO that was originated from OH center dot radicals resulted from flavonoids in extracts. In the flavonoid analyses carried out with high performance liquid chromatography (HPLC) equipment, it was observed that fruit extracts has polyphenolic compounds such as rutin, resveratol, myricetin and naringerin.
Keywords: Morus nigra L. (black mulberry); matured fruit extract (MF); less matured fruit extract (SMF); Fenton reagent (H2O2+FeCl2); DPPH center dot; flavonoids; lipid peroxidation; unsaturated fatty acid